2000
DOI: 10.1023/a:1005188515149
|View full text |Cite
|
Sign up to set email alerts
|

Natural Disaster and Depression: A Prospective Investigation of Reactions to the 1993 Midwest Floods

Abstract: A statewide sample of 1735 Iowa residents, approximately half of whom were victims of the 1993 Midwest Floods, participated in interviews 1 year prior to, and 30 to 90 days after, the disaster. Employing a rigorous methodology including both control-group comparisons and predisaster assessments, we performed a systematic evaluation of the disaster's impact. Overall, the disaster led to true but small rises in depressive symptoms and diagnoses 60-90 days postflood. The disaster-psychopathology effect was not mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
1
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(184 citation statements)
references
References 45 publications
10
169
1
4
Order By: Relevance
“…This study did not include other variables that predicted postdisaster mental health problems (see Brewin et al, 2000;Ozer et al, 2003), such as predisaster depression, prior trauma, and lack of social support (e.g. Ginexi, Weihs, Simmens, & Hoyt, 2000;Galea et al, 2005;Simeon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This study did not include other variables that predicted postdisaster mental health problems (see Brewin et al, 2000;Ozer et al, 2003), such as predisaster depression, prior trauma, and lack of social support (e.g. Ginexi, Weihs, Simmens, & Hoyt, 2000;Galea et al, 2005;Simeon et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…De façon concordante avec cette étude, plusieurs chercheurs ont rapporté le trouble de stress post-traumatique comme étant la condition la plus souvent rencontrée à la suite d'un sinistre (Côté, 1996;Maltais et al, 2001;Norris et al, 2002;Robins, Fischbach, Smith, Cottier, Solomon & Goldring, 1986;Shore et al, 1989;Voguei & Vernberg, 1993). Selon Canino et al (1990) (Ginexi et al, 2000). Phifer (1990) a, quant à lui, trouvé que l'exposition de personnes âgées à des inondations a été associée, 18 mois après les événements, à une augmentation de leurs symptômes dépressifs, de leur anxiété et de leurs symptômes somatiques.…”
Section: Stratégies D'analyseunclassified
“…Ginexi et al (2000) reported a negative correlation between income and depressive symptoms post-disaster. When completing research after the Midwestern floods of 1993, they found that a $5,000 decrease in household income was accompanied by increased flood impact scores.…”
Section: Ptsd Predictive Factors and Responsesmentioning
confidence: 99%
“…These hurricane survivors lost all hope in the system in which they once believed. Ginexi, Weihs, Simmens, and Hoyt (2000) described how the loss of possessions, money, work, and personal resources was a good prediction of post-disaster mental health. Financial stability is an essential piece in instilling hope in victims of disasters who lost their homes and livelihoods (Hobfoll et al, 2007).…”
Section: Ptsd Predictive Factors and Responsesmentioning
confidence: 99%
See 1 more Smart Citation